Interpreting patient-rated outcome measures in adolescent patients following concussion. (19th September 2022) - Snyder Valier, Alison R.; Rogo, Jessica; Bay, R. Curtis; Valovich Mcleod, Tamara C.
ABSTRACT: Objective: To estimate scale scores for patient-reported outcome (PRO) measures that classify patients as improved or unimproved at days 3 and 10 post-concussion. Methods: Data from 187 adolescent patients who sustained a concussion (150 males, 32 females, 5 not reported) were analyzed. Patients completed the Pediatric Quality of Life Inventory (PedsQL), PedsQL Multidimensional Fatigue Scale (MFS), Headache Impact Test (HIT-6), and Global Rating of Change (GROC) on days 3 and 10 post-concussion. Dependent variables: PedsQL total score, 3 MFS subscale scores [general (MFS-GF), sleep (MFS-SLF), cognitive (MFS-CF) fatigue], and HIT-6 total score. Higher scores on PedsQL and MFS indicate better health; lower scores on HIT-6 indicate less impact on headache-related health. GROC ascertained patient-perceived magnitude of change in health status since concussion. Receiver Operating Characteristic Curve analyses estimated PRO cut-point scores that classified patients as improved or unimproved. Results: Day 3 PRO cut-points: PedsQL total = 90; MFS-GF = 73; MSF-CF = 85; MFS-SLF = 81; and HIT-6 total = 54. Day 10 PRO cut-points: PedsQL total = 91; MFS-GF = 85; MFS-CF = 85; MFS-SLF = 90; and HIT-6 total = 51. Conclusions: Our results define PedsQL, MFS, and HIT-6 scores as they relate to perceived improvement following concussive injuries. Cut-point scale scores help clinicians interpret concussion PROs and make informed decisions during the management of patients with concussion.